THE ANALYSIS OF IGNATION TIMING ON THE ENGINE PERFORMANCE OF MATIC MOTORCYCLE USING LPG - Vontas Alfenny Nahan; Sogi Hermanto (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
Indonesia’s crude oil production has been declining in recent years resulting in Government of Indonesia (GoI) to import more. This import gave more pressure to the financial problem GoI faced as the fuel price, especially premium, has been subsidized which reduced the GoI capability to support other sector of developments. This is actually the background of this research which is to support the policy of the GoI to encourage the use of alternative fuels, one of those is Liquefied Petroleum Gas (LPG). The method used in this research is a true experiment method to analyze the performance of the matic motorcycle engine by comparing fuel that is consumed between 5? and 10? angle of crankshaft for ignition timing on petrol and LPG with various rpm ranged from2000 to 6000 rpm). The result shows that LPG consumption at 10?- angle is lower than that of 5?. Ignition time at 10?- angle for LPG is also more optimal than that of 5?. It is concluded also that at the rpm 6000 is the most effective for engine to run at 10?- angle for LPG.